Legislative analysis on quarry rehabilitation in Selangor, Malaysia - Yahya, Zaharah; Ariffin, Mariani; Abdullah, Sabrina Ho (Elsevier, 2018)
The Malaysian State of Selangor has been blessed with an abundant reserve of granite rocks located in the districts of Kuala Langat, Hulu Selangor, Gombak, and Hulu Langat which supply raw materials to develop physical infrastructures including highway roads, building, airports, and townships particularly in Cyberjaya and Putrajaya and supply raw materials to the buildings of the Klang Valley. An active industry, however, comes with shortcomings related to the atmosphere, hydrosphere, lithosphere and biosphere of the ecosystem. In 2009, there were 314 active quarries in Malaysia of which only 12 practiced the best greening effort. Quarry rehabilitation prevents pollution and leads to a cost-effective measure for sustainable quarrying. At present, there is a need to enhance the existing law and policy to ensure the rehabilitation of quarries. Quarry rehabilitation can strike a balance between the need for development, economic aspect, environment, and social aspects in the long term that produces a sustainable quarrying industry that can benefit the Selangor State Government as well as the Federal Government. Generally, this paper aims to identify factors hindering quarry rehabilitation in Selangor. The specific objective of this research is to identify the present status of quarry rehabilitation implementation and examine what the existing legislative framework provides on quarry rehabilitation. By using a qualitative approach, it focuses on Selangor as a case study. A Doctrinal Approach was used to analyze Primary Legal Documents based on the seven Parameters of Quarry Rehabilitation produced by the World Business Council for Sustainable Development (WBCSD) established in 2011. The seven parameters are a vital tool to ensure legal frameworks and policies related to quarry rehabilitation are effective.